2022
DOI: 10.19088/sshap.2022.014
|View full text |Cite
|
Sign up to set email alerts
|

Key Considerations: Tackling Structural Discrimination and COVID-19 Vaccine Barriers for Roma Communities in Italy

Abstract: This brief highlights how structural discrimination and social exclusion shape attitudes to COVID-19 vaccines among Roma communities in Italy, and the role trusted communal and public authorities can play in supporting vaccine uptake and tackling broader exclusions. Contradictions in the Italian state’s response to COVID-19, alongside ongoing forms of exclusion can increase Roma mistrust in state initiatives and prevent vaccine participation. This brief aims to aid and inform local government and public health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There is a complex web of barriers to vaccination for minority ethnic groups. Through ethnographic evidence, our research 3,4 found that access to misinformation on social media was not the main reason for low vaccine uptake. Minority ethnic groups responded to the COVID-19 vaccination campaign based on their socioeconomic circumstances, which were exacerbated by the pandemic; for instance, lack of access to transportation to vaccination centres, barriers in accessing health-care, education, employment, and accommodation, and a previous history of discrimination.…”
mentioning
confidence: 77%
“…There is a complex web of barriers to vaccination for minority ethnic groups. Through ethnographic evidence, our research 3,4 found that access to misinformation on social media was not the main reason for low vaccine uptake. Minority ethnic groups responded to the COVID-19 vaccination campaign based on their socioeconomic circumstances, which were exacerbated by the pandemic; for instance, lack of access to transportation to vaccination centres, barriers in accessing health-care, education, employment, and accommodation, and a previous history of discrimination.…”
mentioning
confidence: 77%
“…The processes of otherness, social 'bordering', and confinement of entire Roma settlements and neighborhoods in Europe during the pandemic intensified socioeconomic inequalities (Sarafian 2022). While it is true that digital disparities can contribute to educational inequalities, these disparities cyclically reinforce and perpetuate socioeconomic inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…While scholars have recognised the need for diversity, this has largely been translated into interventions which adapt health messaging to various linguistic or sociocultural contexts 34–36 39–42. Yet, our evidence suggests that mistrust in vaccines is not only driven by misinformation, but by wider processes of exclusion and discrimination.…”
Section: Principles Of Engagementmentioning
confidence: 93%